A preliminary study on Austronesian interpretation on Ferns as carving motives in the community involving the New Zealander Maori, Indonesian Minangkabau & Malaysian Malay - Mohd. Yaman, Maheran; Wan Abdul Rahman, Wan Mohammad Rafaei (2012)
This study is an early observation from the perspective of a Malay Muslim who has never been to New Zealand. The topic is related to the discipline of architecture as well as landscape architecture. It suggests the link between plant species, fern, with the cultural habits and values of Austronesian communities such as the Maori in New Zealand, the Malay in Sumatra, Indonesia and in Peninsular Malaysia. From a view of a cultural landscape perceptions, this study produce a comparisons on fern as an emblem with a comparisons of carving motif using ferns in other Austronesian community such as Maori in the aninism society in New Zealand and Islam for the Malay in Malaysia and Minangkabau in Indonesia. It is important to study the relationship of fern and carving in the Austronesian and Malay architectures in order to see how environment influenced the society. Moreover, how the environment is use as tool or metaphor to educate society. In term of human geography, the sea farers origins of Maori in New Zealand and Malays in the Malay Archipelago can be traced by the sea route around Polynesian island. Though differs in believes the Austronesian still have their similarities. This is seen in the use of ferns as the carving motives as demonstrate in this study.